Neutrophil gelatinase associated lipocalin (NGAL) in early detection of nephropathy in type 2 diabetic Iraqi patients - kahdem, Ahmed A.; DyabAllawi, Ali A.; Nada, Shaymaa Z.; Turki, Kismat M. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Diabetic nephropathy is a common complication of diabetes mellitus type2. The neutrophil gelatinase Associated lippocallin (NGAL) is an ubiquitous protein consist of 178 amino acid. NGAL can be identified in plasma and urine starting 2- 4 hours after a kidney injury resulting changes in glomerular filtration and tubular reabsorption and with increased secretion in tubular epithelial cells. Objective: This study aimed to evaluate the role of serum Neutrophil Gelatinse Associated Lipocallin (NGAL) in early detection nephropathy. Method : This study was conducted in Medical City, Baghdad Teaching Hospital during the period from December 2015to June 2016.The study included (90) subjects with age range between (30 – 56)years, divided in to three groups , 30 healthy control,30 type 2 diabetic mellitus patients with normal albuminuria and 30 type2 diabetic mellitus patients with micro albuminuria .Body mass index (BMI) was determined, serum NGAL, Fasting serum glucose (FBS),serum creatinine ,serum urea ,andglycated hemoglobin (HbA1c%) were measured for each individual in addition to the concentration of albumin in urine and Glomerular Filtration Rate (eGFR) was calculated. Results:The results of the present study showed that the levels of NGAL, FBS, HbA1c, urea creatinin, were significantly higher in micro albuminuria than normal albuminuria and healthy control. In diabetic patients with micro albuminuria, Serum NGAL shows significant positive correlation with FBS, HbA1c% and urine albumin. Serum NGAL shows significant positive correlation with duration of diabetes but significant negative correlation with GFR. Conclusion:Serum NGAL increased markedly with the reduction of GFR.Serum NGAL is may be considered predictive marker for early detection of diabetic nephropathy in type2 diabetes mellitus.